EFEKTIVITAS MEDIA PEMBELAJARAN EDUKASI SPINNER MATH TERHADAP KEMAMPUAN PENALARAN MATEMATIS SISWA MATERI PERKALIAN DI SEKOLAH DASAR - Amariah, Hanik; Kusmaryono, Imam (Jurnal Pendidikan Sultan Agung, 2025)
The purpose of this study was to test the effectiveness of spinner math educational learning media on students' mathematical reasoning abilities in elementary school multiplication material. This study is a quantitative study of the quasi-experimental type with a One Group Pretest-Posttest Design. The research sample was 24 students of class VB SDN Genuksari 02. The research instruments were tests and questionnaires. Data analysis used the Shapiro Wilk normality test, One Sample t-test, Paired Sample t-test, and N-Gain. The One Sample t-test concluded that there was an achievement of an average KKM value of more than 75, namely 82.88. In the Paired Sample t-test, it can be concluded that there was an increase in the average value before and after using spinner math educational learning media, namely from 32.63 to 82.88. Furthermore, the N-Gain test concluded that the N-Gain value was 74.59% in the range of 56 - 75, which is quite effective. In the questionnaire of students' interest in learning mathematics after using the spinner math educational learning media with an average value of 83 which is very high. Thus, it can be concluded that the spinner math educational learning media is quite effective on students' mathematical reasoning abilities in fraction multiplication material in elementary schools.